Sifat Fisikokimia Enkapsulat Ekstrak Daun Cemcem (Spondias pinnata (L.f) Kurz) dengan Perbandingan Maltodekstrin dan Isolat Protein Whey - Maharani, Ni Putu Devita; Puspawati, Gusti Ayu Kadek Diah; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPA, 2025)
Cemcem leaf (Spondias pinnata (L.f) Kurz) is a plant used in making loloh cemcem, which is rich in bioactive components. Bioactive components in thick extracts are usually more easily damaged when passing through the heating process so that cemcem leaf extracts need to be coated to protect the bioactive components with encapsulation techniques using a coating material such as maltodextrin. Maltodextrin can be combined with other coating materials such as whey protein isolate but it requires a certain ratio. This study aimed to determine the effect of the comparison of maltodextrin and whey protein isolate on the physicochemical properties of cemcem leaf extract encapsulates and to determine the right comparison of maltodextrin and whey protein isolate to produces the best physicochemical properties of cemcem leaf extract encapsulates. The research design used was Randomized Group Design (RAK) with the treatment of the ratio of maltodextrin and whey protein isolate consisting of 8 levels, namely (1:0), (1:2), (1:3), (1:4), (4:1), (3:1), (2:1), and (0:1), repeated twice. Data were analyzed by variance, if there was a significant effect would be continued using Duncan's Multiple Range Test (DMRT). The ratio of maltodextrin and whey protein isolate had a significant effect (P<0.05) on yield, moisture content, solubility, total phenolic content, total vitamin C content, antioxidant activity, encapsulation efficiency, and color intensity (L,a*,b*). The ratio of maltodextrin and whey protein isolate (1:3) produced the best characteristics with a yield value of 83,43 percent, moisture content of 7,76 percent, solubility of 75,92 percent, total phenolic content 84,68 mgGAE/mg, total vitamin C content 41,20 mg/100 g, antioxidant activity of 76,88%, encapsulation efficiency of 89,92 percent, L  value of 84, a* value of 2,5 and b* value of 44 b* value 44 which is defined as flax color.